The need of social support, life attitudes and life satisfaction among parents of children suffering from epidermolysis bullosa - Dorota Mącik; Monika Kowalska-Dąbrowska (Termedia Publishing House, 2015)
Introduction. Epidermolysis bullosa (EB) is a group of rare genetic skin disorders. Much is known about the disease from the medical perspective, but there are still only a few studies about the psychological condition of the patient or his family. The birth of a child with EB may become a trauma for the parents. Parents' feelings also vary depending on the type of EB. Objective. The main aim of the study was to determine whether, and in what way, having a child suffering from EB influences parents' life and psychological well-being. Due to this aim, life satisfaction, life attitudes and the need for social support were measured. Material and methods. Twenty-one parents of ill children were studied (13 mothers, 8 fathers; 16 parents had one child with EB and 5 parents two). Six children suffered from EB simplex, 1 child from junctional EB and 14 from dystrophic EB. The course of the disease was mild in 9 children and severe in 12. As the control group 22 parents of healthy children were chosen. Results. The parents of ill children have a greater need for social support from family, both general, and instrumental, appraisal and emotional. The need for support from medical institutions is at a low level. In life attitudes there are also significant differences. Parents of ill children have a higher level of existential vacuum, and a lower level of life control and life purpose. Also the life satisfaction is lower. Conclusions. The results of our study indicate that a child suffering from EB is a heavy burden for the parents.